Descriptive study of goat external and middle ear through computed tomography and endoscopic evaluation, compared with the human ear - Larissa Leal Coutinho; Pâmella Marletti de Barros; Mariana de Carvalho Leal; Silvio da Silva Caldas Neto; Thiago Freire Pinto Bezerra (Brazilian Journal of Otorhinolaryngology, 2023)
Objective: To describe the external and middle ear of goats, using computed tomography and endoscopic dissection, comparing them with the anatomy of the human ear, aiming to evaluate the viability of this animal model for training in otological endoscopic surgery. Methods: Images of the external and middle ear of goats were produced by computed tomography in the coronal and axial planes and analyzed. The radiological anatomy of the external and middle goat and human ear are described. Some measures of surgical interest were described, such as the length of the external auditory canal, external and internal cross-sectional area of the external auditory canal, middle ear depth, vertical angle of the external auditory canal, length of malleus and incus. After the tomographic study, we analyzed the importance of evaluations through the endoscopic dissection of the goat ear. Results: The bony canal is extremely tortuous and shows a bony prominence with significant elevation near the lower edge of the tympanic membrane. The middle ear has a large tympanic bulla in the hypotympanum region. The malleus is shaped similarly to that of the human, but its handle is located anterior to its head. The mastoid is not pneumatized. Compared to the human mastoid, there was a statistically significant difference in the external and internal cross-sectional area, at the depth of the middle ear, in the vertical angle of the canal and in the length of the incus. Conclusion: Goat morphometric anatomy showed that this model is suitable for surgical simulation in the initial training for endoscopic otological surgery. It is an important contribution to the development of skills to accelerate the subsequent endoscopic otological surgical training in humans, despite some differences found.